2018
DOI: 10.7150/ijbs.23477
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p21 promoted tumorigenesis in the background of telomere dysfunctions induced by TRF2 and Wrn deficiency

Abstract: Werner syndrome (WS) is a rare autosomal recessive progeria disease with genetic instability/cancer predisposition, thus a good model in understanding aging related carcinogenesis. Telomere dysfunction induced cellular senescence is essential in the manifestation of the WS phenotype. Our previous data has shown that p21 (encoded by Cdkn1a gene) could induce cellular senescence and suppress cellular growth of ALT (alternative lengthening of telomere) tumors derived from WS, suggested that p21 might play a key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As a transcription factor, P53 accumulates in senescent cells and directly leads to cell senescence (28). P21 is a negative regulator of the cell cycle, and serves a key role in cellular senescence (29). In the present study, an AS animal model was induced by feeding ApoE −/− mice a HFD for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor, P53 accumulates in senescent cells and directly leads to cell senescence (28). P21 is a negative regulator of the cell cycle, and serves a key role in cellular senescence (29). In the present study, an AS animal model was induced by feeding ApoE −/− mice a HFD for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…As telomeres play important roles in many cellular events including meiosis, nuclear organization, and genomic integrity throughout the lifespan of eukaryotic cells, their dysfunctions associate with various types of diseases including Werner syndrome [84], dyskeratosis congenita [85], Bloom syndrome [86], Fanconi anemia [87], and cancer [88]. Furthermore, there is a close relationship between telomeres/telomerase activity and female infertility caused by ovarian aging [89], polycystic ovary syndrome (PCOS) [90], and premature ovarian failure (POF) [23].…”
Section: Ovarian Function and Telomeres/telomerase Activity In Humansmentioning
confidence: 99%
“…On the other hand, we also observed that some senescent WS MEFs could spontaneously mutate the Trp53 gene and thus diminished p21 function, and these cells were able to form ALT tumors in SCID mice. The exogenous expression of p21 in these cells rebuilt the senescence status ( Jia et al, 2012 ; Si et al, 2018 ). These data were consistent with previous findings and suggested that the p53 or p21 functional loss could also rescue cellular senescence, but with the price of tumorigenesis ( Ferbeyre and Lowe, 2002 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, our data also showed that when we strengthened telomere dysfunction with Wrn deficiency and TRF2 ΔBΔM overexpression ( Wrn –/– TRF2 ΔBΔM ), p21 deficiency with this severe telomere dysfunction resulted in tumorigenesis. Our data suggest that p21 deficiency plays a distinct role in the response to different degrees of telomere dysfunction, reversing aging or tumorigenesis ( Si et al, 2018 ).…”
Section: Introductionmentioning
confidence: 83%